Numerical study of detecting crack initiation in a planar solid oxide fuel cell. Issue 6 (16th July 2020) - Fahs, Imad‐Eddine; Ghassemi, Majid; Fahs, Assil
Abstract: Converting chemical energy into electricity is done by an electrochemical device known as a fuel cell. Thermal stress is caused by high operating temperature, between 700 and 1, 000°C, of solid oxide fuel cell (SOFC). Thermal stress is the main cause of crack initiation and crack propagation. This phenomenon may cause gas leakage, structure instability and cease operation of the SOFC before its lifetime. The aim of this study is to present a method that predicts the initiation of cracks in an anisotropic porous planar SOFC. The coupled governing nonlinear differential equations are solved numerically as for heat transfer, fluid flow, mass transfer, mass continuity, and momentum. An in‐house computer code which is based on computational fluid dynamics, computational structural mechanics and extended finite element method is utilized and developed. This code, according to Darcy and Navier–Stokes thermofluid model, determines the temperature and stress distribution. The results show that the highest thermal stress occurs at the upper corners of cathode and at the lower corners of the anode. The maximum temperature occurs at the middle of the electrolyte cathode and electrolyte anode, while the maximum pressure occurs at the middle of the upper and lower section of the anode and cathode. In addition, the thickness of the cathode electrode at the left side is increased by 1.5%. Finally, the crack initiation occurs at the left side between the upper and lower corners of the cathode.